2020
DOI: 10.1111/cas.14400
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor‐induced COX‐2 regulates metastasis of head and neck squamous cell carcinoma through upregulation of angiopoietin‐like 4

Abstract: Epidermal growth factor receptor (EGFR) expression and activation are the major causes of metastasis in cancers such as head and neck squamous cell carcinoma (HNSCC). However, the reciprocal effect of EGF‐induced COX‐2 and angiopoietin‐like 4 (ANGPTL4) on HNSCC metastasis remains unclear. In this study, we revealed that the expression of ANGPTL4 is essential for COX‐2‐derived prostaglandin E2 (PGE2)‐induced tumor cell metastasis. We showed that EGF‐induced ANGPTL4 expression was dramatically inhibited with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…In view of the fact that ANGPTL4 could regulate the migration and invasion ability of CRC cells, we asked whether ANGPTL4 was involved in the EMT process of CRC, using HCT116 and SW480 cells as models. Induction of molecules involved in the regulation of EMT was earlier shown as dependent on ANGPTL4 expression in head and neck squamous cell carcinoma cells 35 . PI3K/AKT, WNT and other signaling pathways are related to the deterioration of CRC and potential regulators of EMT process and we examined the protein levels of ERK, AKT, and WNT with the corresponding activated proteins to show that upon silencing ANGPTL4, the levels of p-ERK42/44 significantly increased in both cell lines.…”
Section: Discussionmentioning
confidence: 90%
“…In view of the fact that ANGPTL4 could regulate the migration and invasion ability of CRC cells, we asked whether ANGPTL4 was involved in the EMT process of CRC, using HCT116 and SW480 cells as models. Induction of molecules involved in the regulation of EMT was earlier shown as dependent on ANGPTL4 expression in head and neck squamous cell carcinoma cells 35 . PI3K/AKT, WNT and other signaling pathways are related to the deterioration of CRC and potential regulators of EMT process and we examined the protein levels of ERK, AKT, and WNT with the corresponding activated proteins to show that upon silencing ANGPTL4, the levels of p-ERK42/44 significantly increased in both cell lines.…”
Section: Discussionmentioning
confidence: 90%
“…In breast cancer, HDAC6 was frequently upregulated in the cancerassociated fibroblasts(CAFs) and increased the expression of COX-2/PGE2 by regulating STAT3 activation (20), leading to poor survival outcomes. In addition, the aberrant activation of EGF (21), KRAS (22), p38MAPK (23,24) signals, which frequently present in cancers, also induce COX-2 expression, thus to mediate immunosuppression.…”
Section: The Activation Of Cox-2/pge2 Pathway In Cancermentioning
confidence: 99%
“…And it has been reported that the high expression of HSPA5 can protect cancer cells from immune surveillance, and inhibition of its expression can promote cell apoptosis and inhibit tumor growth [ 24 , 25 ]. Angiopoietin-like4 (ANGPTL4) is highly expressed in various tumors, which is closely related to tumor growth and metastasis, such as hepatocellular carcinoma [ 26 ], breast cancer [ 27 ], head and neck squamous cell carcinoma [ 28 ] and melanoma [ 29 ]. And ANGPTL4 participates in the construction of GRG signature in lung adenocarcinoma to predict the survival and metastasis of patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%